Cocoa Liquor Increases SOD Activity in Wistar Rats Experiencing Oxidative Stress - Dwi Putra, Kartika Wahyu; Wirjatmadi, Bambang; Purwanto, Bambang; Adriani, Merryana (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a